2015
DOI: 10.1007/s00192-015-2685-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for de novo stress urinary incontinence following extensive pelvic reconstructive surgery

Abstract: Continent women with advanced pelvic organ prolapse (POP) > 66 years, with DM or low MUCP and FUL values during preoperative urodynamic evaluation have higher risk of developing de novo SUI; therefore, we suggest counselling such women for concomitant PRS and anti-incontinent surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
48
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 26 publications
3
48
1
1
Order By: Relevance
“…Women aged 50 years or older had twice the risk of OSUI compared to those younger than 50 years (P<0.005). This is comparable to Lo et al who found that women older than 66 years were 2.86 times at greater risk of developing de novo SUI postoperatively (19). In addition, age is an important confounding factor in relation to concomitant medical illnesses which may aggravate urinary incontinence.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Women aged 50 years or older had twice the risk of OSUI compared to those younger than 50 years (P<0.005). This is comparable to Lo et al who found that women older than 66 years were 2.86 times at greater risk of developing de novo SUI postoperatively (19). In addition, age is an important confounding factor in relation to concomitant medical illnesses which may aggravate urinary incontinence.…”
Section: Discussionsupporting
confidence: 76%
“…Reena et al found postmenopausal women had a statistically significant risk of developing OSUI (17). This is supported by Lo et al who showed postmenopausal status is independent predictors for de novo SUI following extensive POP repair (19). In addition, estrogen replacement is thought to alleviate incontinence by facilitating proliferation and maturation of urethral mucosa in postmenopausal women (24).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, varieties of LUTS including, de novo overactive bladder89, voiding dysfunction and de novo urinary stress incontinence10 may occur after mesh implantation surgery for POP. It would be difficult to differentiate if the LUTS were brought about by a transient physiologic phenomenon secondary to the surgical procedure or a result of a worrisome reaction to the mesh.…”
mentioning
confidence: 99%
“…One patient developed dSUI despite the standard urodynamics with prolapse reduction using ring pessary. Lo et al noted a prevalence of dSUI on extensive pelvic reconstructive surgery of 11.1% . Patients aged > 66 years, with diabetes mellitus, and low mean urethral closure pressure and functional urethral length during preoperative urodynamic evaluation, have higher risk of developing dSUI …”
Section: Discussionmentioning
confidence: 99%